CURRENT PERSPECTIVES OF ONCOPLASTIC BREAST SURGERY IN PAKISTAN (The Research of Medical Science Review, 2025)
The foundation of oncoplastic breast surgery is the idea of rapid rebuilding tailored to the specific tumor. It uses a combination of distant and local methods to preserve breast symmetry, texture, and appearance without sacrificing the oncological result. Because the majority of surgeons treating breast cancer are either general surgeons or breast surgeons without expertise in reconstructive or oncoplastic breast surgery, the current narrative review was designed to highlight the current state and future of oncoplastic breast surgery in low- and middleincome countries, where its use in surgical practice remains insignificant. Furthermore, women are forced to conceal their breast disease due to a lack of financial resources, a lack of knowledge regarding oncoplastic breast surgery procedures, discomfort from disfigurement, and cultural taboos. More information about oncoplastic breast surgery is needed in a developing nation like Pakistan. For breast surgeons to use these approaches in their practice, specialized oncoplastic breast surgery training centers, fellowship programs, workshops, and webinars must be established.